Mechanistic divergence between SOS response activation and antibiotic-induced plasmid conjugation in Escherichia coli - Ruoxuan Zhao; Arkadiusz Nawrocki; Jakob Møller-Jensen; Gang Liu; John Elmerdahl Olsen; Line Elnif Thomsen (Microbiology Spectrum, 2025)
ABSTRACT The SOS response is a critical DNA damage repair mechanism in bacteria, designed to counteract genotoxic stress and ensure survival. This system can be activated by different classes of antimicrobial agents, each inducing the SOS response through different mechanisms. Moreover, it has been observed that certain antibiotics can enhance conjugative plasmid transfer frequencies. However, while previous studies have suggested that the SOS response contributes to horizontal transfer of certain genes, its role in plasmid conjugation remains unclear. In this study, we investigated the relationship between the SOS response and conjugation of IncI1 and IncFII plasmids harboring various blaCTX-M resistance genes. Results showed that cefotaxime and mitomycin C induced both the SOS response and conjugation, while ciprofloxacin induced the SOS response without affecting conjugation frequencies. Further analysis of SOS mutants, ranging from constitutively inactive to hyper-induced states, revealed no correlation between SOS levels and conjugation frequencies, despite upregulation of tra gene expression in a SOS hyper-induced strain. Proteomic analysis revealed that cefotaxime-induced conjugation was associated with increased transfer and pilus protein expression. In contrast, the SOS hyper-induced strain displayed limited upregulation of plasmid-encoded proteins, suggesting post-transcriptional regulation. Additionally, putative LexA binding sites on the IncI1 plasmid revealed potential SOS-mediated regulation of plasmid genes, highlighting the interaction between the SOS response and plasmid, although it did not significantly affect conjugation.IMPORTANCEPlasmids play a critical role in the dissemination of antibiotic resistance through conjugation. Recent research suggests that the use of antibiotics not only selects for already resistant variants but further increases the rate of plasmid-encoded conjugative transmission by increasing expression of the conjugative system. At the same time, these antibiotics are known to induce the stress-related SOS response in bacteria. To be able to counteract an antibiotic-induced increase in conjugative transfer of resistance plasmid, there is a need for a fundamental understanding of the regulation of transmission, including whether this happens through activation of the SOS response. In this research, we show that antibiotic-induced conjugation and induction of the SOS response happen through different mechanisms, and thus that future strategies to control the spread of antibiotics cannot interfere with the SOS response as its target.